GESTIÓN DE LA TECNOLOGÍA DE LA INFORMACIÓN Y SU INFLUENCIA EN LOS PROCESOS ADMINISTRATIVOS DE LA DIRECCIÓN DE PLANIFICACIÓN Y ORDENAMIENTO TERRITORIAL DEL MUNICIPIO DE URDANETA. - CORTEZ MORA, WALTER VICENTE (2023)
The management of information technology, better known as ICT, is considered a highly influential tool in the administrative processes of companies, whether public or private, as it is an information storage bridge that allows companies to digitize and easily obtain documentation related to the processes carried out within the institutions, allowing at the same time to optimize time and improve the quality of the information. The technology management system allows information to be stored and processed through computer devices and in turn presents it to subordinates and users, if applicable. In this way, the use of automated information through technology is of great importance. in saving time and resources by simplifying and streamlining management processes and in turn in decision making.